Measurement of Relative Coronary Blood Flow in a Rabbit Model of Acute Myocardial Ischemia by the Optical Mapping Method with RH-237 - Soontaree Petchdee; Francis L Burton; Godfrey L Smith (Agriculture and Natural Resources, 2010)
A method was developed to produce acute regional ischemia and reperfusion in a rabbit heart that was used in conjunction with optical voltage recordings and the method was validated for imaging relative myocardial perfusion. The left anterior descending branch of the coronary artery in an isolated Langendorff perfused rabbit heart was ligated using a snare to allow acute blockage and reperfusion of an apical region of the myocardium. The voltage-sensitive dye, RH237, was used to map electrical activity. RH237 is virtually non-fluorescent in free solution, but becomes fluorescent when partitioned into the cardiac membrane. Partitioning is very rapid (less than 1s) and so measuring the rate and extent of rise of fluorescence in the whole heart could be used to quantify local perfusion rates. The use of 0.33 μmole RH237 per gram tissue of the heart resulted in 50% maximal binding and this technique revealed the extent and shape of the ischemic region in the isolated perfused rabbit heart, in conjunction with electrical activity and using a single fluorescent dye.